Design of smart light/shadow detection for market umbrella - Muhammad Salman Irfan, Mohd Sanusi (2019)
Market umbrella sometimes is also known as patio umbrella is an outdoor leisure type of umbrella. The existing market umbrellas are not able to give fully shade. Furthermore, it does not stable in a sandy surface. This smart market umbrella is designed to rotate 360˚ and move according to the direction of the sunlight. This umbrella consists of four Light Dependent Resistor (LDR) sensor, 12V Direct Current (DC) motor, gear, 12V dry battery and Arduino Uno R3 board. The rotation on the umbrella depends on the sensor value by comparing the value on average top and average bottom whether it exceeds or less than 20. This umbrella has been modified with minimum cost by adding DC motor, sensor and gear to rotate the umbrella automatically for full shade. Addition of 15 cm x 10cm of mild steel plate at the base improves the stability of umbrella. In the end, the addition of the fabrications to the umbrella is done and perfectly working just as wanted with plenty of room for improvement that can be added.